Palladium-Catalyzed Synthesis of 1H-Pyrazolo[4,3-c]quinolines and 4-Anilinoquinoline-3-carbonitriles from 4-Chloroquinoline-3-carbaldehydes - Wang, Chao; Tang, Caifei; Li, Zhiming; Wang, Quanrui (Synthesis, 2015)
Novel 1H-pyrazolo[4,3-c]quinolines and 4-anilinoquinoline-3-carbonitriles were prepared from readily accessible 4-chloroquinoline-3-carbaldehyde hydrazones by palladium-catalyzed intramolecular C–N bond formation and concurrent hydrazine N–N bond fission. These two classes of functionalized quinolines were chromatographically separable, and both are of biological interest. The ratio of the two products was found to be temperature-dependent; by changing the reaction temperature, either the pyrazoloquinoline or the anilinoquinolinecarbonitrile can become the dominant product.
Keywords: hydrazones; palladium; cross-coupling; fused-ring systems; nitriles; pyrazoloquinolines